Knowledge, attitudes, and breast feeding practices of postnatal mothers: A cross sectional survey - Poreddi, Vijayalakshmi; Thyagarajan, Susheela; Dharmalingam, Mythili (International Journal of Health Sciences, 2015)
Background: Breast feeding has several benefits for both the infants and mothers. However, despite strong evidences in support of breast feeding its prevalence has remained low worldwide. The objective of the present study was to examine the knowledge and attitude towards breast feeding and infant feeding practices among Indian postnatal mothers. Methodology: A cross sectional descriptive study was carried out among randomly selected postnatal mothers at Pediatric outpatient department at a tertiary care center. Data was collected through face-to-face interview using a structured questionnaire. Results: Our findings revealed that a majority (88.5%) of the mothers were breast feeders. However, merely 27% of the mothers were exclusive breast feeders and only 36.9% initiated breast feeding within an hour. While mothers have good knowledge on breast feeding (12.05±1.74, M±SD), the average score of the Iowa Infant Feeding Scale (IIFAS) (58.77±4.74, M ±SD) indicate neutral attitudes toward breast feeding. Mothers those who were currently breast feeding (58.83 ± 4.74) had more positive attitudes than non- breastfeed mothers (45.21±5.22). Conclusion: Our findings also show that the level of exclusive breast-feeding was low. Thus, it is important to provide prenatal education to mothers and fathers on breast-feeding. We also recommend strengthening the public health education campaigns to promote breast-feeding.